2018
DOI: 10.3892/mmr.2018.9720
|View full text |Cite
|
Sign up to set email alerts
|

Gambogic acid prevents angiotensin II‑induced abdominal aortic aneurysm through inflammatory and oxidative stress dependent targeting the PI3K/Akt/mTOR and NF‑κB signaling pathways

Abstract: Gamboge is the dry resin secreted by Garcinia hanbaryi Hook.f, with the function of promoting blood circulation and anti-cancer effects, detoxification, hemostasis and killing insects. It is also used for the treatment of cancer, brain edema and other diseases. Gambogic acid is the main effective constituent of Gamboge. The present study tested the hypothesis that the effect of Gambogic acid prevents angiotensin II-induced abdominal aortic aneurysm (AAA), and explored its underlying mechanism. It was demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…It is also worth mentioning that novel chemo-photothermal synergistic therapy targeted on CD44 -positive inflammatory macrophages is being developed for the treatment of atherosclerosis ( 58 ). In addition, mTOR , a signaling molecule also called the mechanistic target of rapamycin, has been identified as a key factor in the PI3K/Akt/ mTOR or the AMPK/ mTOR signaling pathway ( 59 , 60 ). The overactivation of mTOR signaling accelerates AAA expansion via affecting the phenotype transition of VSMCs, macrophages infiltration, MMPs expression, and inflammatory cytokine production ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also worth mentioning that novel chemo-photothermal synergistic therapy targeted on CD44 -positive inflammatory macrophages is being developed for the treatment of atherosclerosis ( 58 ). In addition, mTOR , a signaling molecule also called the mechanistic target of rapamycin, has been identified as a key factor in the PI3K/Akt/ mTOR or the AMPK/ mTOR signaling pathway ( 59 , 60 ). The overactivation of mTOR signaling accelerates AAA expansion via affecting the phenotype transition of VSMCs, macrophages infiltration, MMPs expression, and inflammatory cytokine production ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…The overactivation of mTOR signaling accelerates AAA expansion via affecting the phenotype transition of VSMCs, macrophages infiltration, MMPs expression, and inflammatory cytokine production ( 61 ). Hence, mTOR is also reckoned as a potential target for AAA drug therapy including rapamycin, metformin (MET) and Gambogic acid ( 59 , 60 , 62 ). As for the integrin family (including ITGB1, ITGAV, ITGA1 , etc.…”
Section: Discussionmentioning
confidence: 99%
“…inhibitor (Ortega et al, 2019), niacin (Horimatsu et al, 2019), licochalcone A, a traditional Chinese medicine (Hou, Yang, & Zheng, 2019), and gambogic acid, a derivative of resin (Liu, Shan, & Li, 2019), which inhibited AAA development. In contrast, vascular smooth muscle-specific deficiency of the alpha subunit of the heterotrimeric G stimulatory protein, responsible for receptor-stimulated cAMP generation and activation of protein kinase A pathway (Qin et al, 2019), promoted AAA formation in mouse models.…”
Section: Miscellaneous Other Interventions Recently Investigatedmentioning
confidence: 99%
“…Gambogic acid is the main effective constituent of Gamboge. Liu et al demonstrated that Gambogic acid prevents angiotensin II induced AAA through inflammatory and oxidative stress dependent targeting of the PI3 K/Akt/mTOR and NF-κB signaling pathways in mice [49]. Licochalcone A (LA), a chalcone derived from liquorice, exhibits multiple biological activities, including anti-oxidation and anti-inflammation.…”
Section: Impact Of Medical Management On Aneurysm Growthmentioning
confidence: 99%